Evidence of Illegitimate Recombination Between Two Pasteurellaceae Plasmids Resulting in a Novel Multi-Resistance Replicon, pM3362MDR, in Actinobacillus pleuropneumoniae - Li, Yinghui; da Silva, Giarlã Cunha; Li, Yanwen; Rossi, Ciro C.; Fernandez Crespo, Roberto; Williamson, Susanna M.; Langford, Paul R.; Bazzolli, Denise Mara Soares; Bossé, Janine T. (Frontiers in Microbiology, 2018)
Evidence of plasmids carrying the tetracycline resistance gene, tet(B), was found in the previously reported whole genome sequences of fourteen UK, and four Brazilian, isolates of Actinobacillus pleuropneumoniae. Isolation and sequencing of selected plasmids, combined with comparative sequence analysis, indicated that the four Brazilian isolates all harbour plasmids that are nearly identical to pB1001, a plasmid previously found in Pasteurella multocida isolates from Spain. Of the UK isolates, 13/14 harbour plasmids that are (almost) identical to pTetHS016 from Haemophilus parasuis. The remaining UK isolate, MIDG3362, harbours a 12666 bp plasmid that shares extensive regions of similarity with pOV from P. multocida, which carries blaROB-1, sul2 and strAB genes, as well as with pTetHS016. The newly identified multi-resistance plasmid, pM3362MDR, appears to have arisen through illegitimate recombination of a pTetHS016-like plasmid into the stop codon of the truncated strB gene in pOV. All of the tet(B)-carrying plasmids studied were capable of replicating in Escherichia coli, and predicted origins of replication were identified. A putative origin of transfer (oriT) sequence was also identified in these plasmids, however attempts to mobilize them from an RP4-encoding E. coli donor strain were not successful, indicating that specific conjugation machinery may be required.